2023
DOI: 10.1371/journal.pone.0283755
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of malaria in pregnancy among women attending antenatal care at a large referral hospital in northwestern Uganda: A cross-sectional study

Abstract: Background Malaria in pregnancy contributes to substantial morbidity and mortality among women in Uganda. However, there is limited information on the prevalence and factors associated with malaria in pregnancy among women in Arua district, northwestern Uganda. We, therefore, assessed the prevalence and factors associated with malaria in pregnancy among women attending routine antenatal care (ANC) clinics at Arua regional referral hospital in north-western Uganda. Methods We conducted an analytic cross-secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…In Ghana, one out of every five pregnant women in the antenatal care clinic had a P. falciparum infection [18]. Mangusho et al have shown that 26.1% of pregnant women in Uganda had P. falciparum malaria [11]. Recently, in their meta-analysis of 24 studies (n = 14,087 pregnant women), Boltena et al [19] indicated that the pooled prevalence of malaria in sub-Saharan Africa was 33.0%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In Ghana, one out of every five pregnant women in the antenatal care clinic had a P. falciparum infection [18]. Mangusho et al have shown that 26.1% of pregnant women in Uganda had P. falciparum malaria [11]. Recently, in their meta-analysis of 24 studies (n = 14,087 pregnant women), Boltena et al [19] indicated that the pooled prevalence of malaria in sub-Saharan Africa was 33.0%.…”
Section: Discussionmentioning
confidence: 99%
“…However, primiparas were reported to be associated with placental malaria in the Blue Nile state in Sudan [4]. In Uganda, a recent study reported no association between age and malaria during pregnancy [11]. In Nigeria [5] and in West Ethiopia [6] malaria during pregnancy was associated with age and parity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Difficulty fighting off infections and potential neurological problems are also harmful effects of malaria in pregnancy (5). In Uganda, the prevalence of malaria in pregnancy ranges from as low as 8.9% to as high as 50% depending on the region (6). The standard of care for IPTp in Uganda is for women to receive at least two doses of SP/Fansidar during their second and third trimester (7).…”
mentioning
confidence: 99%